Expression of early growth responsive gene-1 in the visual cortex of monocular form deprivation amblyopic kittens - Haobo Fan (BMC, 2021)
Abstract Purpose The present study compared the expression of early growth responsive gene-1 (Egr-1) in visual cortex between amblyopia kittens and normal kittens, and to explore the role of Egr-1 in the pathogenesis of amblyopia. Methods A total of 20 healthy kittens were randomly divided into deprivation group and control group with 10 kittens in each group. Raised in natural light, and covered the right eye of the deprived kittens with a black opaque covering cloth. Pattern visual evoked potentials (PVEP) were measured before and at the 1st, 3rd and 5th week after covering in all kittens. After the last PVEP test, all kittens were killed. The expression of Egr-1 in the visual cortex of the two groups was compared by immunohistochemistry and in situ hybridization. Results PVEP detection showed that at the age of 6 and 8 weeks, the P100 wave latency in the right eye of deprivation group was higher than that in the left eye of deprivation group (P < 0.05) and the right eye of control group (P < 0.05), while the amplitude decreased (P < 0.05). The number of positive cells (P < 0.05) and mean optical density (P < 0.05) of Egr-1 protein expression in visual cortex of 8-week-old deprivation group were lower than those of normal group, as well as the number (P < 0.05) and mean optical density of Egr-1 mRNA-positive cells (P < 0.05). Conclusions Monocular form deprivation amblyopia can lead to the decrease of Egr-1 protein and mRNA expression in visual cortex, and then promote the occurrence and development of amblyopia.